-7x+1=-x+1

Simple and best practice solution for -7x+1=-x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+1=-x+1 equation:


Simplifying
-7x + 1 = -1x + 1

Reorder the terms:
1 + -7x = -1x + 1

Reorder the terms:
1 + -7x = 1 + -1x

Add '-1' to each side of the equation.
1 + -1 + -7x = 1 + -1 + -1x

Combine like terms: 1 + -1 = 0
0 + -7x = 1 + -1 + -1x
-7x = 1 + -1 + -1x

Combine like terms: 1 + -1 = 0
-7x = 0 + -1x
-7x = -1x

Solving
-7x = -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-7x + x = -1x + x

Combine like terms: -7x + x = -6x
-6x = -1x + x

Combine like terms: -1x + x = 0
-6x = 0

Divide each side by '-6'.
x = 0

Simplifying
x = 0

See similar equations:

| (16x+4)=36 | | 60+1.6Y=176 | | 11+12m+m^2= | | X(2-x)+b(2-b)=5 | | 2x^2+17x-84=0 | | 9x=4-7x | | x^2+29x+17= | | 7q^2-2pq-7q+2p= | | X=110+-1Y | | 1.6X+1.6Y=176 | | (X+15)+x+39=180 | | y(x-8)-5(x-8)= | | 2x+2b=5 | | -32xy-98x^2= | | 2(3b^2+2)+4b-5= | | 6x^2+12x-48= | | 12p^2=8-10p | | R*1.6(R+10)*1.6=176 | | 2(2x+3)=2x-12 | | 2x-4(x-2)=2x+4 | | 12m^2+37m-10=0 | | (3x-18)+2x+x=180 | | 60r-50=15r | | x^2-11=4x | | 2m^2+6m+1m+6=0 | | 6.28=3.14x | | 4x-20+30=2x | | (2x-8)+90=180 | | 10(324)+14K= | | 8y+44=4y | | 10(243)+14K= | | 2m^2+7m+6=0 |

Equations solver categories